ANALISIS YURIDIS TERHADAP HAK-HAK KEPEMILIKAN KENDARAAN BERMOTOR DIKAITKAN DENGAN PEMBAYARAN PAJAK (SUATU STUDI PADA DINAS PENDAPATAN PROVINSI ACEH) - FACHRUR ROUZI (PREMISE LAW JURNAL, 2017)
The results found out that Aceh Province is an autonomy region, as related to the Ownership Rights over Motor Vehicle related to its tax payment to Aceh Province, the tax obligation is attached to the taxpayer which is determined according to the vehicle registration and identification stages; thus, the vehicle which is registered outside Aceh tax administration area has to be transferred. Administrative ownership/ possession of a vehicle is different from civil ownership/ possession; therefore, if there is a vehicle which right is not transferred yet administratively in Aceh Province, its tax obligation is not transferred yet. The legal protection for the vehicle which tax is paid on behalf of another person’s name is that it cannot be accepted to be processed because the tax obligation is attached to the taxpayer so that the payment made by someone whose identity is different from the vehicle registration and identification has to be made with a power of attorney. Keywords: Ownership/ Possession Rights, Motor Vehicle Tax, Tax Payment in Aceh.